Lima Kode Roland Barthes dalam Film Bumi Manusia Karya Salman Aristo - Nurhalisah Nurhalisah; Rina Andriani; Mahpudoh Mahpudoh (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This research is motivated by the numerous signs, symbols, and meanings contained in Salman Aristo's film Bumi Manusia, which represent the social, cultural, and historical realities of the colonial era. This study aims to describe Roland Barthes's five codes: hermeneutic, proairetic, semitic, symbolic, and cultural codes in Bumi Manusia. The study used a descriptive qualitative approach with Roland Barthes's semiotic theory. Data in the form of dialogue, scenes, character expressions, and visual elements containing signs were collected through documentation techniques and analyzed using the concept of lexia and Barthes's five codes. The results show that all five of Roland Barthes's codes are found in Bumi Manusia and mutually construct the narrative's meaning structure. The hermeneutic code builds the story's puzzle, the proairetic code drives the sequence of actions, the semitic code strengthens the character's characterization, the symbolic code represents the conflicting values ​​and power, while the cultural code presents historical, cultural, and social system references during the colonial era. These findings indicate that Bumi Manusia is an audiovisual work rich in sign systems and capable of representing meaning in depth through Roland Barthes's five semiotic codes.